Prevention, policy, and public health - Eyler, Amy A.; Chriqui, Jamie F.; Moreland-Russell, Sarah; Brownson, Ross C. (Oxford University Press, 2016)
The greatest public health victories of the last century - public sanitation, vehicle safety measures, limits on smoking and tobacco use - have all been facilitated by public policies. While policy is an unparalleled tool for effecting change in public health, most professionals are unprepared to plan, apply, or study policy in a consequential way. This title provides a basic foundation for students, professionals, and researchers to be more effective in the policy arena. It offers information on the dynamics of the policymaking process, theoretical frameworks, analysis, and policy applications.